Advances in hydrogel-based vascularized tissues for tissue repair and drug screening - Ying Wang; Ranjith Kumar Kankala; Caiwen Ou; Aizheng Chen; Zhilu Yang (Bioactive Materials, 2022)
The construction of biomimetic vasculatures within the artificial tissue models or organs is highly required for conveying nutrients, oxygen, and waste products, for improving the survival of engineered tissues in vitro. In recent times, the remarkable progress in utilizing hydrogels and understanding vascular biology have enabled the creation of three-dimensional (3D) tissues and organs composed of highly complex vascular systems. In this review, we give an emphasis on the utilization of hydrogels and their advantages in the vascularization of tissues. Initially, the significance of vascular elements and the regeneration mechanisms of vascularization, including angiogenesis and vasculogenesis, are briefly introduced. Further, we highlight the importance and advantages of hydrogels as artificial microenvironments in fabricating vascularized tissues or organs, in terms of tunable physical properties, high similarity in physiological environments, and alternative shaping mechanisms, among others. Furthermore, we discuss the utilization of such hydrogels-based vascularized tissues in various applications, including tissue regeneration, drug screening, and organ-on-chips. Finally, we put forward the key challenges, including multifunctionalities of hydrogels, selection of suitable cell phenotype, sophisticated engineering techniques, and clinical translation behind the development of the tissues with complex vasculatures towards their future development.